Sistem Pendukung Keputusan Kelulusan Peserta Pelatihan Menggunakan Metode Naïve Bayes - Jajang Nurjaman; Andrianingsih Andrianingsih (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
A decision support system (DSS) is a system that helps decision making in a particular process or situation. In the context of trainee permits, SPK can be used to help predict graduation or not based on several relevant factors, the main objective of this research is to change the system calculation method from manual to automatic. The Center for Tourism and Creative Economy Human Resource Development (PPSDM Parekraf) uses this system to help automate graduation calculations from manual to automatic by inputting several values ​​(Pre & Post Test, Behavior, Assignments and Quizzes, Reports and Comprehensive Test) with all the value provisions reached the test threshold (70). The Naive Bayes method is one of the general classification methods used by SPK and is based on the Bayes theorem with the assumption that each feature or factor used in classification is independent of one another. This system is designed to facilitate an effective and efficient decision-making process in transmitting training participants whether they can continue to the next level of training. This research was carried out in the period from March to June 2023 at PPSDM Parekraf. The data studied uses and analyzes by taking samples of ongoing training data. Hopefully, this SPK will help with more accurate and efficient decisions in determining the graduation of Basic Tourism training participants, the current conditions regarding value processing are still carried out manually. This system is recommended to be used as a medium or tool to support the results of participants' agreements which initially used manual calculations to become automatic. To test the data, it is done by collecting the data and values ​​of the training participants, then preprocessing the data using the Naïve Bayes method into a decision support system.